Spis lenników majątku ziemskiego Brody (Herrsch aft Pförthen ) z 10 sierpnia 1688 roku = The vassal census of 10th august 1688 in the Brody Land Ownership (Herrschaft Pforthen) - Maciejewski, Marcin (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents unknown vassal census of August 10, 1688 from Brody Land Ownership (Herrschaft Pforthen) made on the occasion of the vassal homage paid to Ulrich von Promnitz after taking over in Brody goverments. This is first publication in the Polish historiography concering vassal homage paid by nobles from the land ownership, that is part of Lower Lausatia and nowadays is to be found in the present boundaries of Poland. The article supplements the studies of German historians such as Gotz von Houwald and Rudolf Lehmann, thereby giving a fuller viev of the nobility living in the second half of the 17th century in Lower Lusatia, especially an Brody Land Ownership.
Keywords: Brody; Promnitz, von; spis lenników; vassal census